Blockchain‐based trusted data sharing among trusted stakeholders in IoT. (1st August 2019) - Shi, Peichang; Wang, Huaimin; Yang, Shangzhi; Chen, Chang; Yang, Wentao
Summary: Sharing trusted data among trusted stakeholders is very important to large‐scale Internet of Things (IoT) applications. However, the entities and organizations involved in IoT naturally lack trusted relationships, which poses significant challenges to the above vision. Specifically, the first challenge is to ensure that the data in the physical world can be objectively and truly injected into the information world of IoT. The second is to ensure the credibility of the entities' identities in IoT. The third is to ensure the authenticity of data, the credibility of identity, and the reliable transmission of data when a third trusted party is unable to provide the expected trusted services. In view of the above challenges, this paper proposes a secure and lightweight triple‐trusting architecture (SLTA), which fully uses a blockchain‐related supporting technology. The architecture includes an oracle‐based data collection mechanism, which ensures that the data collected from edge devices of IoT cannot be modified, and the distributed identity management mechanism, which enhances personal privacy, security, and control of digital identities. Furthermore, a series of innovative designs for applying the blockchain to special large‐scale cooperation scenario in IoT are proposed, which is also a part of the key mechanisms of the SLTA. The innovative design includes a new software‐defined blockchain structure model and a lightweight Byzantine fault‐tolerant algorithm that provides credible support for decentralized data collection, identity management, and data transfer, as well as low‐overhead sequential storage mechanism.